(untitled) (Research, Society and Development, 2022)
Objective: to report the experience of a nursing resident in the Multiprofessional Residency Program (RMS) in Comprehensive Care in Orthopedics and Traumatology. Methodology: This is an experience report developed from experiences from March 2020 to January 2022, in two public hospitals in the city of Santarém, western region of Pará. The analysis of this study took place in a critical and reflective way and as it was not a research, it was not submitted to the Research Ethics Committee. Results: The role of the nursing resident is carried out through rotation in the various sectors of hospital institutions such as the operating room, medical and surgical clinic, urgency and emergency sector in trauma and orthopedics outpatient clinic, with pediatric, adult and elderly patients. It involves nursing assessment, pre, trans and postoperative, care for multiple trauma patients, making orthopedic immobilizations, surgical instrumentation, dressing and guidelines for self-care. Final Considerations: It is concluded that the RMS contributes to the acquisition of technical-scientific knowledge that allows a new conduct in the face of professional practice, making the resident able to provide safe and systematized assistance in the health service and attention to users with orthotraumatological disorders within the scope of the national health service.